Assessing Genomic Diversity, Connectivity, and Riverscape Genetics Hypotheses in the Endangered Rough Hornsnail, Pleurocera Foremani, Following Habitat Disruption. (21st October 2021) - Redak, Caitlin A; Williams, Ashantye' S; Garner, Jeffrey T; Halanych, Kenneth M; Whelan, Nathan V
Abstract: The southeastern United States is home to some of the richest biodiversity in the world. Over the last 200 years, however, rapid industrialization and urbanization have threatened many natural areas, including freshwater habitats. River impoundments have also rapidly altered freshwater habitats, often resulting in species extirpation or extinction. The Coosa River in Alabama experienced one of the largest faunal declines in modern history after impoundment, making it an ideal system for studying how invertebrate species are affected by reservoir creation. One such species, the Rough Hornsnail, Pleurocera foremani, is an endangered freshwater snail in the family Pleuroceridae. We sampled all known localities of P. foremani and used 2bRAD-seq to measure genetic diversity. We assessed riverscape genomic patterns across the current range of P. foremani and measured gene flow within and between impoundments. We also investigated the degree to which P. foremani displays an isolation by distance pattern and conforms to broad hypotheses that have been put forth for population genetics of riverine species like the Mighty Headwater Hypothesis that predicts greater genetic diversity in headwater reaches compared with mainstem populations. Like most other freshwater species, a pattern of isolation by distance was observed in P. foremani . We also found that Coosa River dams are a barrier to gene flow, and genetic fragmentation of P. foremani is likely to increase. However, gene flow appeared common within reservoirs and tributaries. Additionally, we found that spatial genetic structure of P. foremani deviates from what is expected under the Mighty Headwaters Hypothesis, adding to a growing body of research suggesting that the majority of genetic diversity in low-dispersing gastropods is found in mainstem populations.